2010
DOI: 10.1002/mnfr.201000445
|View full text |Cite
|
Sign up to set email alerts
|

Evidences on three relevant obesogenes: MC4R, FTO and PPARγ. Approaches for personalized nutrition

Abstract: Obesity is a complex disease that results from the interaction between lifestyle (dietary patterns and sedentary habits) and genetic factors. The recognition of a genetic basis for human obesity has driven to identify putative causal genes to understand the pathways that control body mass and fat deposition in humans as well as to provide personalized treatments and prevention strategies to fight against obesity. More than 120 candidate genes have been associated with obesity‐related traits. Genome‐wide associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 118 publications
(107 reference statements)
2
81
0
6
Order By: Relevance
“…Pro12Ala variant of PPARG2 gene is one of the most studied genes as potentially linked to obesity phenotypes (Razquin et al 2011). Previous meta-analysis had associated the Ala12 minor allele with a higher BMI (Masud 2003;Tonjes et al 2006;Galbete et al in press), and this study confirmed in a larger sample of aged subject the association of the Ala12 allele with obesity risk.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Pro12Ala variant of PPARG2 gene is one of the most studied genes as potentially linked to obesity phenotypes (Razquin et al 2011). Previous meta-analysis had associated the Ala12 minor allele with a higher BMI (Masud 2003;Tonjes et al 2006;Galbete et al in press), and this study confirmed in a larger sample of aged subject the association of the Ala12 allele with obesity risk.…”
Section: Discussionsupporting
confidence: 75%
“…FTO and PPARG2 gene variants for obesity risk have been widely studied (Razquin et al 2011). Several meta-analyses showed an increased body mass index (BMI) in subjects with the Ala allele of the PPARG2 gene (Masud 2003;Tonjes et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with monogenic obesity, in polygenic obesity each mutation leads to a variant that confers susceptibility, requiring additionally the presence of other variants and an obesogenic environment to determine the obese phenotype (Razquin et al 2011). There are two main approaches for the detection and analysis of a candidate gene in body weight regulation: linkage analysis and association studies.…”
Section: Genetic Approach For Common Obesitymentioning
confidence: 99%
“…Melanocortin-4 receptor (MC4R), a G-protein-coupled receptor, is involved in appetite regulation and energy balance (Barb et al, 2004;Seeley et al, 2004;Razquin et al, 2011). In humans, more than 150 mutations in the MC4R gene have been found, some of which are associated with obesity (Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%